The existence of equilibrium when excess demand obeys the weak axiom. - Quah, J (Nuffield College (University of Oxford), 2004)
This paper gives a non-fixed point theoretic proof of equilibrium existence when the excess demand function of an exchange economy obeys the weak axiom. The proof is simple and geometrically intuitive, and it also permits a weakening of the continuity assumption on the excess demand function.